Non-Negligible Factors Influence Tree-Ring-Based Temperature Reconstruction and Comparison over Mid-Latitude China - Zeyu Zheng; Zhenqian Wang; Yufang Zhang (Atmosphere)
Warm-season mean maximum temperature changes over mid-latitude regions have been attracting increasing attention amid the background of global warming. In this study, we present three tree-ring width chronologies: Tongbai Mountain (TBM; 1916–2014), Shimen Mountain (SMM; 1663–2014), and Xinlong (XL; 1541–2014), derived respectively from the eastern Qinling Mountains, north–central China, and the eastern Tibetan Plateau. Therein, TBM and SMM are newly developed, while XL is a reanalysis. Correlation analysis with climatic factors reveals that these three chronologies exhibit the highest correlation with the May–July mean maximum temperature. Based on these chronologies, we conducted reconstructions of the May–July mean maximum temperature. Spatial correlation analysis of each reconstruction with concurrent observed data, as well as comparisons with nearby temperature reconstructions, indicates their large-scale representativeness. However, during the common period of 1916–2014, the three chronologies show weak correlations with each other at the interannual timescale. Furthermore, the 11-year running correlation coefficients among the three reconstructions fluctuated during this common period. Additionally, fluctuations were observed between the reconstructions from SMM and XL during the overlapping period of 1668–2009, suggesting that tree-ring-based temperature reconstructions may be inconsistent when compared over mid-latitude China. These inconsistent changes can be attributed to the regional differences in the May–July mean maximum temperature change, the influence of different precipitation signals on the maximum temperature, and the El Niño–Southern Oscillations.